Suppression of refractory arrhythmias by aprindine in patients with the Wolff-Parkinson-White syndrome. Issue 12 (December 1977) - Reid, P R; Greene, H L; Varghese, P J
Abstract : Four patients with supraventricular tachycardia associated with the Wolff-Parkinson-White syndrome were refractory to conventional pharmacological therapy and received aprindine hydrochloride intravenously and orally. Electrophysiological studies disclosed that intravenous aprindine caused increased refractoriness and slowed conduction in the atria, atrioventricular node, ventricles, and accessory pathway. The ability to induce supraventricular tachycardia with timed atrial and ventricular premature stimuli was totally abolished in all 4 patients after intravenous aprindine. Oral aprindine therapy, twice daily thereafter, provided symptomatic relief of the supraventricular tachycardia without significant side effects. Aprindine is useful in the management of supraventricular tachycardia associated with Wolff-Parkinson-White and may offer significant advantages over currently available therapy.